25.1k views
2 votes
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth.

x^2 - 6 = -x

2 Answers

2 votes

Answer:

The final answers are x = 2 OR x = -3.

Explanation:

Given the equation is x^2 -6 = -x

Rewriting it in quadratic form as:- x^2 +x -6 = 0.

a = 1, b = 1, c = -6.

Using Quadratic formula as follows:- x = ( -b ± √(b² -4ac) ) / (2a)

x = ( -1 ± √(1 -4*1*-6) ) / (2*1)

x = ( -1 ± √(1 +24) ) / (2)

x = ( -1 ± √(25) ) / (2)

x = ( -1 ± 5 ) / (2)

x = (-1+5) / (2) OR x = (-1-5) / (2)

x = 4/2 OR x = -6/2

x = 2 OR x = -3

Hence, final answers are x = 2 OR x = -3.

User Mathieu Schmitt
by
5.1k points
3 votes

Answer:

Thus, the two root of the given quadratic equation
x^2-6=-x is 2 and -3 .

Explanation:

Consider, the given Quadratic equation,
x^2-6=-x

This can be written as ,
x^2+x-6=0

We have to solve using quadratic formula,

For a given quadratic equation
ax^2+bx+c=0 we can find roots using,


x=(-b\pm√(b^2-4ac))/(2a) ...........(1)

Where,
√(b^2-4ac) is the discriminant.

Here, a = 1 , b = 1 , c = -6

Substitute in (1) , we get,


x=(-b\pm√(b^2-4ac))/(2a)


\Rightarrow x=(-(1)\pm√((1)^2-4\cdot 1 \cdot (-6)))/(2 \cdot 1)


\Rightarrow x=(-1\pm√(25))/(2)


\Rightarrow x=(-1\pm 5)/(2)


\Rightarrow x_1=(-1+5)/(2) and
\Rightarrow x_2=(-1-5)/(2)


\Rightarrow x_1=(4)/(2) and
\Rightarrow x_2=(-6)/(2)


\Rightarrow x_1=2 and
\Rightarrow x_2=-3

Thus, the two root of the given quadratic equation
x^2-6=-x is 2 and -3 .

User Tnrvrd
by
5.1k points